2011
DOI: 10.2217/nnm.11.41
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Scavenger Receptor A Mediates The Uptake of Gold Colloids by Macrophages In Vitro

Abstract: Aims While numerous studies have reported on nanoparticle uptake by phagocytic cells, the mechanisms of this uptake are poorly understood. A metastudy of research focusing on biological particulate matter has postulated that nanoparticles cannot be phagocytosed and therefore must enter cells via pinocytosis. The purpose of this study was to identify the route(s) of uptake of gold nanoparticles in vitro and to determine if these route(s) depend on particle size. Materials & Methods The parent RAW264.7 cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 30 publications
3
65
0
3
Order By: Relevance
“…Although both the in vivo and in vitro testing of AuNPs of different sizes are known to sometimes produce contradictory results 17,18 , we first focused on the 35 nm AuNPs as an example for microscopic detection since this size is easier to examine. Our method was based on correlating the signals of the transmitted high energy electrons and the scattered low energy ones coming mainly from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Although both the in vivo and in vitro testing of AuNPs of different sizes are known to sometimes produce contradictory results 17,18 , we first focused on the 35 nm AuNPs as an example for microscopic detection since this size is easier to examine. Our method was based on correlating the signals of the transmitted high energy electrons and the scattered low energy ones coming mainly from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…For example, phagocytosis has been believed for quite some time to be associated uniquely with the uptake of large particles (.1 mm). However, there are several reports that show the phagocytosis of nanometer-sized particles such as viruses (Clement et al 2006;Ghigo et al 2008), gold (Krpetic et al 2010;Franca et al 2011), silver (Park et al 2011), and polymer nanoparticles (Lunov et al 2011), as well as quantum dots .…”
Section: Sizementioning
confidence: 99%
“…It was reported that gold nanoparticles with sizes below 100 nm were phagocytosed via scavenger receptor-mediated phagocytosis. 30 Tsai et al 31 also demonstrated that gold nanoparticles with a size of 4 nm showed the highest uptake in the macrophages based on the number of nanoparticles taken up per cell, compared with those sized 11, 19, 35, and 45 nm. The 4 nm gold nanoparticles exhibited the highest potency in inhibiting tumor necrosis factor (TNF)-α production related to TNR9-mediated innate immune systems.…”
mentioning
confidence: 98%